The Prevalence, Profile, and Risk Factor of Patients with Ulcerative Colitis at Dr. Saiful Anwar Malang General Hospital - Syifa Mustika; Nanik Triana (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2016)
Background: The prevalence ulcerative colitis (UC) in RSCM Jakarta in 1991-1995 is 2.5%. The disease affects men and women at similar rates or slightly more common in women than in men. Age of onset follows a bimodal pattern, with a peak at 15-25 years and a smaller one at 55-65 years, although the disease can occur in people of any age. The precise etiology of UC is not well understood. UC is precipitated by a complex interaction of environmental (cigarretes, diet, non-steroidal anti-inflammatory drug/NSAID, etc), genetic, and immunoregulatory factors. This study aimed to identify the prevalence, profile and risk factor of ulcerative colitis in Dr. Saiful Anwar General Hospital Malang.Method: This is a retrospective survey analysis from medical record which was taken from 2170 patients who underwent colonoscopy in Dr. Saiful Anwar General Hospital Malang from January 2010 to December 2014. Demographic setting (sex, age), clinical features, lifestyle, diagnosis based on colonoscopy were analyzed as the variables.Results: Total patients with UC was 176 patients. The prevalence of UC during 2010-2014 was 8.2% at Dr. Saiful Anwar General Hospital. There was a similar prevalence of sex between male and female patients, in which 95 (53.4%) were male and 81 (46.6%) were female. The average age of patients with UC was 41,6 years. Most patients were presented with abdominal pain (32.90%) and weight loss (42.1%). The diagnosis based on colonoscopy were pancolitis (36%), proctosigmoiditis/proctitis (31.81%), and left-sided colitis (21.9%). The risk factors of UC identified in this study were current smoker, use of NSAIDs/traditional herbs/potion and fiber diet. Majority of ulcerative colitis study samples were non-smoker (75%), not consuming herbal treatment/NSAID (60.22%), and rarely consuming fiber (36.93%). There is a significan correlation between frequency of fiber diet and UC (r = -0.106,  p = 0.000).Conclusion: The prevalence of UC was 8.2%  in our hospital with men and women were equally affected, and average age was 41.6 years. Patients presented with various clinical symptoms, most are abdominal pain and weight loss. The most frequent diagnosis were pancolitis, proctosigmoiditis/proctitis, and leftside colitis. There is a significant correlation between frequency of fiber diet and UC (r = -0.106,  p = 0.000).Keywords : ulcerative colitis, prevalence, profile, risk factors